2020
DOI: 10.3390/pharmaceutics12050428
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Drug-Assisted Bone Healing: Advances and Challenges in Drug Delivery Approaches

Abstract: Bone defects of critical size after compound fractures, infections, or tumor resections are a challenge in treatment. Particularly, this applies to bone defects in patients with impaired bone healing due to frequently occurring metabolic diseases (above all diabetes mellitus and osteoporosis), chronic inflammation, and cancer. Adjuvant therapeutic agents such as recombinant growth factors, lipid mediators, antibiotics, antiphlogistics, and proangiogenics as well as other promising anti-resorptive and anabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 240 publications
0
30
0
Order By: Relevance
“…Furthermore, several attempts have been undertaken to specifically target BMPs, PTH or OPG in order to improve bone integrity [ 256 ]. Finally, biocompatible polymers may provide novel strategies to enhance bone healing in patients with metastatic bone cancers [ 257 ].…”
Section: Diagnosis and Therapy Of Bone Metastasesmentioning
confidence: 99%
“…Furthermore, several attempts have been undertaken to specifically target BMPs, PTH or OPG in order to improve bone integrity [ 256 ]. Finally, biocompatible polymers may provide novel strategies to enhance bone healing in patients with metastatic bone cancers [ 257 ].…”
Section: Diagnosis and Therapy Of Bone Metastasesmentioning
confidence: 99%
“…In the previous sections, it was also shown that different drugs and drug concentrations, respectively, are particularly beneficial, depending on the stage of tissue regeneration. Thus, release materials possessing multiple release mechanisms or materials that release the active ingredient in response to a certain stimulus are the focus of recent research [456][457][458][459][460][461].…”
Section: Drug Release Concepts Mechanisms and Applications In Stem Cell-based Osteogenesis And Angiogenesismentioning
confidence: 99%
“…Refinements in surgical procedures, implant construction and postoperative care have greatly increased patient outcomes for complex injuries and abnormalities caused by high energy trauma, cancer, developmental deformity and surgery. [101][102][103][104][105] Extensive soft tissue damage, inadequate surgical techniques, infections, and biomechanical instability can lead to large defects with limited internal regenerative potential. These defects represent a significant surgical challenge, associated with high socio-economic costs and have a high impact on the quality of life of patients.…”
Section: Translation Of Bone Engineering Concept From Bench To Bedsidementioning
confidence: 99%